High molecular weight chitosan based particles for insulin encapsulation obtained via nanospray technology - Prudkin Silva, Cecilia Raquel (2020)
The objective of this work was to obtain Chitosan (CS) based particles for Insulin (INS) encapsulation, via nanospray drying of a feeding solution containing equal amounts of both components (0.1% w/v total solids content). The process was performed at pH 3 which is out of the range for electrostatic interactions to occur. The analysis involved the nanoparticles (NP) characterization in the solution before drying (pH 3) by dynamic light scattering (DLS) and after re-hydration at different pHs (3< pH < 11). The dried product was characterized by Fourier-transform spectroscopy (FTIR), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). FTIR allowed detecting the chemical groups involved in INS-CS interactions. The encapsulation efficiency of the glassy NP was 62.3 ± 0.32% as determined by HPLC. Upon powder re-hydration, NP of diameter <200 nm were obtained, with a minority of them exceeding the micron. The change in the shape and temperature of the main endothermic DSC peak and the higher Tg value of the NP would confirm the increase in INS thermal stability when entrapped in a CS matrix. In terms of biological activity an in-vitro system was assayed. 3T3-L1 fibroblasts were exposed to INS and InsulinChitosan nanoparticles (INS-CS NP). Both treatments showed AKT phosphorylation, which is an indication of AKT activation. The activity of AKT plays an essential role in cell metabolism (lipid and glucose), growth, proliferation, polarity, among others. This activity is a measure of the upstream cell signals, i.e. INS’s receptor activity. Phosphorylated AKT was detected during the assay time for INS-CS NP, showing remarkable differences respect to single INS. Nanodrying technology could be used to trap INS into CS matrix keeping the specific hormone functions and protecting it from the hostile conditions of the body.